WHAT WE LEARN ABOUT HOSPITAL SERVICE QUALITY DURING PANDEMIC COVID-19: AN INVESTIGATION OF SATISFACTION POST-PANDEMIC SITUATION - Silalahi, Andri Dayarana K.; Sormin, Surmida; Lumbangaol, Chrisna (UNIKA Santo Thomas, 2023)
During the COVID-19 pandemic, hospitals provided vital health services to the community. This is especially true for patients who have been exposed to COVID-19. There is considerable literature on hospital patient satisfaction, but the practical details of how service quality affects patient satisfaction during the COVID-19 pandemic require further investigation. In light of this, this study proposes a model of patient satisfaction based on the quality of service provided during the COVID-19 pandemic. To collect data, a questionnaire was administered to 200 hospital patients treated during the COVID-19 pandemic. In order to analyze the data, SPSS 25 software was used to perform multiple regression analysis. It was found that empathy had the most significant impact on patient satisfaction. Despite this, it appears that patients do not prioritize the physical facilities, responsiveness, or reliability of a hospital since these factors do not significantly impact patient satisfaction. The assurance factor is one of the factors that negatively impact satisfaction. Accordingly, this study recommends that hospitals provide services to patients emphasizing assurance, responsiveness, reliability, and physical facilities in order to increase patient satisfaction during the COVID-19 outbreak. As the improvement in service quality will affect patient satisfaction, it will also affect the patient's confidence in the hospital.